Real-World Case Studies Showing the Effective Use of Azelaic Acid in the Treatment, and During the Maintenance Phase, of Adult Female Acne Patients - Layton AM; Dias da Rocha MA (Dove Medical Press, 2023)
Alison M Layton,1 Marco Alexandre Dias da Rocha2 1Skin Research Centre, Hull York Medical School, University of Hull, Hull, UK; 2Federal University of São Paulo, São Paulo, BrazilCorrespondence: Marco Alexandre Dias da Rocha, Federal University of São Paulo, Rua Oscar Pinheiro Coelho, 115 casa 04. Caxingui, São Paulo, Brazil, Email marcoderm@hotmail.comAbstract: Acne Vulgaris is a chronic inflammatory skin disease, and one of the most prevalent inflammatory dermatoses among teenagers, affecting more than > 95% of boys and 85% of girls. Adult female acne (AFA) is a subtype of acne, pragmatically defined as affecting women over the age of 25. The clinical presentation of AFA may be distinguished from adolescent acne according to some key clinical and psychosocial characteristics. The etiopathogenic factors and the chronic clinical course that are implicated in AFA make management complex and challenging. A frequent tendency to relapse makes the requirement for maintenance therapy highly likely. Therefore, AFA typically requires a specific, tailored therapeutic approach. This paper presents six challenging case studies that demonstrate the efficacy of azelaic acid gel (AZA) in adult female acne. The six cases use AZA as monotherapy, as part of a combination regimen at treatment initiation, or as maintenance treatment (which is frequently required in this adult population). The positive outcomes achieved in this case series demonstrate that AZA can be efficacious, result in excellent patient satisfaction in mild to moderate adult female acne, and can be effective as a maintenance therapy.Keywords: acne vulgaris, adult female acne, azelaic acid, skin conditions, inflammation